Bahasa Inggris - Agus Edy Pramono; Iman Setyadi; Aminudin Zuhri; Anissa Puspa Dewi; Nanik Indayaningsih (MBI, 2025)
This paper compares the electrical conductivity of LLDPE-carbon composite materials, LLDPE-carbon-aluminum composites, and LLDPE-carbon-copper composites. Doping with aluminum (Al) and copper (Cu) metal powders influences electrical conductivity in carbon-based polymer composite materials. Adding metal powders as secondary fillers to a mixture of conductive carbon powders and LLDPE can decrease electrical conductivity. This is due to the agglomeration or clustering of metal powders within the polymer matrix, which disrupts conductive pathways and diminishes the efficiency of electrical charge transfer. The impact of filler type and quantity on electrical conductivity in composite materials was examined, and the findings revealed that factors such as the filler's amount, shape, and dispersal significantly affect the composite's electrical resistance properties. Increasing the amount of metal powder filler raises the composite's viscosity, reducing adhesion between the metal and polymer fillers while promoting metal-to-metal contacts.